(untitled) (Ciudades, 2018)
This article will discuss the residentialization of French peripheries, an urban renewal process based on the replacement of large groups of social housing by small, closed residential units. These units are protected by important control and surveillance measures, the new type of urban fabric thus planned seeks to correct the perception of insecurity and to modify the uses of the common spaces of the periphery, attracting the middle class to strongly stigmatized urban environments. Presenting the social theories in which this process has been based, and the results of fieldwork carried out in the periphery of Paris, we will discuss both the adaptation of the population to these new environments, and the type of city that would be emerging out of that process.